Photocatalytic activity study of ZnO modified with nitrogen–sulfur co-doped carbon quantum dots under visible light. (18th July 2022) - Liu, Huadong; Li, Hewei; Du, Kezhen; Xu, Haoxuan
Abstract : Enhanced degradation rate of RhB under visible light by N, S-CQDs-modified ZnO. Abstract : The development of high-efficiency photocatalytic materials responsive to visible light is one of the most effective ways to address the environmental threats posed by organic dyes in industrial wastewater. In this paper, novel visible-light-responsive nitrogen–sulfur co-doped carbon quantum dots modified ZnO (ZnO/N, S-CQDs) composites with a significantly enhanced photocatalytic degradation performance of Rhodamine B (RhB) were successfully synthesized. Under visible light, the photocatalytic degradation efficiency reached 98.7% over the optimal composite. Besides, the degradation obeyed the pseudo-first-order kinetics model with a photocatalytic rate constant ( k ) of 0.0473 min −1, which was around 3.71 times higher than that of pure ZnO nanoparticles (0.01273 min −1 ). In addition, the morphology, size and elemental composition of the ZnO/N, S-CQDs were characterized using TEM, SEM, XRD, FT-IR, and XPS which confirmed the successful synthesis of the composites. Photoluminescence (PL) and transient photocurrent response results indicated an increase in the carrier separation efficiency of ZnO/N, S-CQDs. Based on the active species removal experiment, superoxide radicals (˙O 2− ) played a leading role in the photocatalytic reactions and a possible photocatalytic degradation mechanism was revealed. These further demonstrate that the N, S-CQDs with varying properties contributed significantly to the enhanced photocatalytic activity of ZnO. Overall, the present method follows the principle of green economy, and novel N, S-CQDs provide a feasible approach for the development of photocatalytic performance of ZnO.